2014
DOI: 10.1523/jneurosci.1844-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Endocannabinoid-Mediated Modulation of Rostromedial Tegmental Nucleus Drive onto Dopamine Neurons in Sardinian Alcohol-Preferring Rats

Abstract: The progressive predominance of rewarding effects of addictive drugs over their aversive properties likely contributes to the transition from drug use to drug dependence. By inhibiting the activity of DA neurons in the VTA, GABA projections from the rostromedial tegmental nucleus (RMTg) are well suited to shift the balance between drug-induced reward and aversion. Since cannabinoids suppress RMTg inputs to DA cells and CB1 receptors affect alcohol intake in rodents, we hypothesized that the endocannabinoid sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
38
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 46 publications
8
38
0
Order By: Relevance
“…In agreement with our previous study, we found that a subpopulation of RMTg neurons is sensitive to painful stimuli (Lecca et al, 2012). Reduced RMTg-evoked inhibition of DA neurons is associated with their enhanced spontaneous discharge and with vulnerability to drug and alcohol abuse (Lecca et al, 2012;Melis et al, 2013Melis et al, , 2014. Although chronic peripheral neuropathy did not induce changes in firing activity of RMTg neurons, we observed a shortened RMTg-evoked inhibition of DA cells, which is suggestive of a reduced GABA release onto DA cells and, in turn, of their disinhibition, although we cannot exclude that electrical stimulation might excite passing fibers from other regions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our previous study, we found that a subpopulation of RMTg neurons is sensitive to painful stimuli (Lecca et al, 2012). Reduced RMTg-evoked inhibition of DA neurons is associated with their enhanced spontaneous discharge and with vulnerability to drug and alcohol abuse (Lecca et al, 2012;Melis et al, 2013Melis et al, , 2014. Although chronic peripheral neuropathy did not induce changes in firing activity of RMTg neurons, we observed a shortened RMTg-evoked inhibition of DA cells, which is suggestive of a reduced GABA release onto DA cells and, in turn, of their disinhibition, although we cannot exclude that electrical stimulation might excite passing fibers from other regions.…”
Section: Discussionsupporting
confidence: 92%
“…Firing rate and burst firing of VTA DA neurons is controlled by inhibitory and excitatory afferents (Marinelli et al, 2006;Morikawa and Paladini, 2011). Among inhibitory inputs to DA cells, the RMTg plays an important role, as it densely innervates VTA DA cells with GABAergic afferents (Barrot et al, 2012;Lecca et al, 2011;Lecca et al, 2012;Melis et al, 2014). This nucleus receives a dense excitatory innervation from the lateral habenula and, therefore, is involved in neural circuits mediating aversion (Balcita-Pedicino et al, 2011;Jhou et al, 2009aJhou et al, , 2009b.…”
Section: Discussionmentioning
confidence: 99%
“…The GABAergic tail of the ventral tegmental area (tVTA) (Kaufling et al, 2009(Kaufling et al, , 2010aPerroti et al, 2005), or rostromedial tegmental nucleus (RMTg) (Jhou et al, 2009a(Jhou et al, , 2009b, is a mesopontine structure, which exerts a major inhibitory control over dopamine cells of the VTA and substantia nigra pars compacta (SNc) (Bourdy and Barrot, 2012;Matsui et al, 2014;Sánchez-Catalán et al, 2014). The tVTA has been implicated in motor functions (Bourdy et al, 2014;Lavezzi et al, 2015), responses to drugs of abuse (Jalabert et al, 2011;Jhou et al, 2012Jhou et al, , 2013Kaufling et al, 2010b;Lavezzi et al, 2012;Lecca et al, 2011Lecca et al, , 2012Matsui and Williams, 2011;Matsui et al, 2014;Melis et al, 2014;Rotllant et al, 2010), and reward prediction error (Hong et al, 2011). In addition, stimulation of the habenulo-tVTA pathway favors avoidance behaviors (Stamatakis and Stuber, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive previous work has shown that activation of G q/11 -coupled receptors in dopamine neurons stimulates 2-AG formation and retrograde modulation of synaptic transmission (Kortleven et al, 2012; Melis et al, 2004a; 2004b; 2014; Pan et al, 2008; Riegel and Lupica, 2004; Tung et al, 2016; Wang et al, 2015). In our experiments, activating mGluR, orexin, or neurotensin receptors rapidly inhibited I A by 20–35% and mimicked the magnitude of effects of 100 nM-1 ÎĽM exogenous 2-AG.…”
Section: Discussionmentioning
confidence: 99%
“…Midbrain dopamine neurons are well-suited for this purpose, because immunohistochemistry suggests that they lack expression of CB 1 receptors (Herkenham et al, 1991; Mátyás et al, 2008) and an abundance of evidence shows that they synthesize (Mátyás et al, 2008) and release 2-AG, which acts in a retrograde manner to strongly regulate both glutamatergic (Kortleven et al, 2012; Labouèbe et al, 2013; Melis et al, 2004a; 2004b) and GABAergic (Melis et al, 2014; Pan et al, 2008; Riegel and Lupica, 2004; Tung et al, 2016; Wang et al, 2015) inputs. To isolate direct effects on intrinsic excitability from synaptically-mediated effects, we used a preparation of acutely dissociated midbrain dopamine neurons, which retain their distinctive electrophysiological properties, including regular pacemaking (Hainsworth et al, 1991; Puopolo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%